Clinicopathological and Genetic Characteristics of Patients of Different Ages with Diffuse Sclerosing Variant Papillary Thyroid Carcinoma - Kim, Soo Young; Shin, Su Jin; Lee, Dong Gi; Yun, Hyeok Jun; Kim, Seok Mo; Chang, Hojin; Chang, Hang Seok; Shin, Hyunjung; Lee, Yong Sang (Cancers, 2023)
Diffuse sclerosing variant papillary thyroid carcinoma (DSVPTC) is commonly observed in young patients, with a median age at diagnosis in the third decade of life. Further, the risk of recurrence is higher for DSVPTC than for classical PTC. Therefore, this study aimed to describe the clinicopathological and genetic characteristics of patients of different ages with DSVPTC. We retrospectively reviewed 397 patients who underwent thyroidectomy for DSVPTC at Gangnam Severance Hospital, Yonsei University, from January 2005 to December 2017. The mean age at diagnosis was 36.7 ± 11.6 years, with most patients (163, 41.1%) aged 31–40 years. DSVPTC was predominant in women (276, 69.5%). We observed recurrence in 46 (11.6%) patients, with regional nodal recurrence being the most common type of recurrence (32 patients, 69.6%). The mean tumour size was larger in younger patients than in older patients. DSVPTC was more aggressive in paediatric patients with a larger-sized tumour, more common multiplicity, and lateral neck metastasis. Through random sampling, we selected 41 patients by age group and examined the mutations in 119 genes using next-generation sequencing. BRAF, KRAS, and TERT displayed relatively higher mutation rates than other genes. DSVPTC displays different clinical, pathological, and molecular profiles than classical PTC. The BRAF, KRAS, and TERT mutations are the most important, with age-specific differences.
Keywords: BRAF; diffuse sclerosing variant papillary thyroid carcinoma; gene; K-Ras; papillary thyroid cancer; TERT; thyroid malignancy